Array - Ramadhani, Hana Fairuz; Nurchayati, Nurchayati (Character Jurnal Penelitian Psikologi, 2023)
This research investigates the issues and coping strategies of early adult women struggling with the death of their mother. It uses case study qualitative approach. The data are collected through semi-structured interviews. Based on narrative analysis of three early adult women, who happened to be the only daughter in the family, and who had had to cope with the loss of their mother, this research revealed several issues faced by the participants, including (1) the difficulty in balancing responsibilities due to dual roles; (2) the unsupportive external environment; (3) the remarriage father; (4) the fear of entering romantic relationships; (5) the financial difficulties; (6) a distant relationship with the father; (7) loss of motivation in academics; and (8) being an only child and not having a partner, leading to feelings of loneliness. Additionally, all participants demonstrated adaptive coping strategies by utilizing a combination of problem-focused coping, emotion-focused coping, and religious/spiritual coping. The use of these adaptive coping strategies enabled the participants to effectively navigate their lives after the death of their mothers.